Eliciting Welfare Preferences from Behavioural Data Sets - Rubinstein, A.; Salant, Y. (Review of Economic Studies, 2012)
An individual displays various preference orderings in different payoff-irrelevant circumstances. It is assumed that the variation in the observed preference orderings is the outcome of some cognitive process that distorts the underlying preferences of the individual. We introduce a framework for eliciting the individual's underlying preferences in such cases and then demonstrate it for two cognitive processes—satisficing and small assessment errors.